Efektivitas Manajemen Bimbingan Konseling: Layanan, Penilaian, dan Instrumen Evaluasi di SMA Negeri 1 Parigi - Dede Mulyana; Dede Anggraeni; Galang Pratama Sudiar; Hilmy Farhani Ali (J-STAF : Siddiq, Tabligh, Amanah, Fathonah, 2024)
This research aims to describe the effectiveness of guidance and counseling management, particularly in services, assessment, and evaluation instruments at SMA Negeri 1 Parigi. A qualitative descriptive method was employed, collecting data through interviews, observations, and documentation. The research findings indicate that the factual evaluation instruments for comprehensive guidance and counseling programs do not currently meet the required validity criteria in the evaluation context. An alternative hypothetical model was successfully designed, and a refined and suitable model of evaluation instruments was produced. Furthermore, the study reveals that guidance and counseling planning focuses on designing services that meet the students' needs, implementation begins with forming organizational structures, execution follows the program with some constraints, supervision adheres to specific principles, and evaluation is conducted to measure the success of the planned program.